Design and implementation of impact evaluations of MSD projects: The case of InovAgro - Ghebru, Hosaena; Grant, William; Smart, Jenny (Development Alternatives Incorporated, 2021)
This paper identifies the lessons learned from the InovAgro MSD programme from a value chain perspective as well as in cross-cutting services in Northern Mozambique’s agricultural sector. The International Food Research Institute (IFPRI) and DAI provide observations concerning what worked well and what did not work well in terms of the collaborative design and execution of the project and its impact evaluation.